Mountain valleys, alluvial fans and oases: Geomorphologic perspectives of the mixed agropastoral economy in Xinjiang (3000–200 BC) - Yin, Chen; Zhang, Junna; Yu, Xuetong (Frontiers in Earth Science, 2023)
Xinjiang serves as a hub for trans-Eurasian exchange. The Xinjiang hominids are supposed to be greatly influenced by the environment due to the fragile ecology and arid climate. As the territory with the most significant and complex geomorphic units in Inner Asia, Xinjiang features a diverse spectrum of geomorphic forms, including mountains, basins, deserts, river valleys, and oases. This paper presents a systematic summary of the geomorphic locations of 127 Bronze Age to early Iron Age (3000–200 BC) sites and cemeteries in Xinjiang and their economic strategies, exploring the different economic choices of ancient humans who lived in other geomorphic units, and how they adapted to their microenvironments. We have divided Xinjiang into five regions: the Junggar Basin, the Tarim Basin, the Western Tianshan Mountains, the middle Tianshan Mountains, and the Eastern Tianshan Mountains. Our study shows that there were different agropastoral economic modes in different geographical units. Roughly bounded by the Tianshan Mountains, the economy in northern Xinjiang was heavily based on animal husbandry, while oasis farming was popular in the Southern Xinjiang reigon. From the perspective of geomorphology, most sites are situated in mountain valleys, alluvial fans, and oases regions with surface water sources and fine-textured soil cover. Sites near mountains were more likely to develop a mixed pastoral-hunting economy, and oasis communities of a specific size were more likely to build a mixed agricultural-pastoral economy. In large river valleys or alluvial fans, it is expected that settlement clusters and large central settlements will grow, leading to the emergence of social complexity. This study will help to understand the complex “man-land” dynamics between 3000 and 200 BC in Xinjiang.